2022
DOI: 10.1186/s12902-022-00951-6
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study on the association between poor sleep quality in junior high school students and high hemoglobin A1c level in early adults with higher body mass index values

Abstract: Background Few epidemiological studies have been performed to clarify the association between glucose metabolism disorders in early adults (20 years old) and physiological and environmental factors, including body mass index (BMI) in junior high school days. Therefore, we examined the association between hemoglobin A1c (HbA1c) level and body size (BMI) in early adulthood and lifestyles, including sleep habits and BMI in junior high school days in Shika town, a small town in Japan, by conducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This could be due to functional differences or a greater resiliency of metabolic processes in children compared to adults. Some studies on the relationship between sleep and insulin sensitivity found that sleep quality is a greater predictor of insulin sensitivity than sleep duration (Clark et al, 2016; Kasahara et al, 2022; Thumann et al, 2020). Considering this, a more wholistic analysis of sleep in future studies may help elucidate the nature of the relationship between sleep and glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to functional differences or a greater resiliency of metabolic processes in children compared to adults. Some studies on the relationship between sleep and insulin sensitivity found that sleep quality is a greater predictor of insulin sensitivity than sleep duration (Clark et al, 2016; Kasahara et al, 2022; Thumann et al, 2020). Considering this, a more wholistic analysis of sleep in future studies may help elucidate the nature of the relationship between sleep and glycaemic control.…”
Section: Discussionmentioning
confidence: 99%